PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN BERBASIS ANIMASI SEBAGAI UPAYA PENINGKATAN PROFESIONALISME GURU PADA SMK NEGERI 1 JENEPONTO - Imran Djafar; Hasyrif Hasyrif; Nurdiansah Nurdiansah; Akbar Bahtiar; Sitti Harlina (Indonesian Collaboration Journal of Community Services, 2023)
Community service is a series of tridharma at tertiary institutions, so that activities at SMKN I Jeneponto are the implementation of training activities for making Animation-Based Learning Media as an effort to increase teacher professionalism. However, the problem that is often faced by subject teachers in carrying out their activities within the scope of SMK Negeri 1 Jeneponto is making teaching materials and materials using methods that are not optimal, there is still a lack of understanding about the use of Information Technology and the Use of Software Applications that support learning media, especially in applications presentation processing and application software for animation creation. For this reason, training on making animation-based learning media was held to meet their needs. This activity was carried out in four stages, namely the pre-activity stage, the preparation stage, the training implementation stage, and the activity evaluation stage. This activity was attended by 25 Jeneponto Vocational School 1 teachers who were directly accompanied by speakers from the Undipa PKM team. The result of the activity is an increase in the ability of all teachers. This is evidenced by the results of a user satisfaction survey. In addition, from the design of the animated learning media designs that were made, the best and most interactive ones were selected and had an increase in the quality of the animation designs